Le concept de représentation en didactique des sciences : sa nécessaire composante épistémologique et ses conséquences - Christian Orange; Denise Orange Ravachol (Nantes Université, 2013)
In science education, the notion of conception has necessarily an epistemological reference, despite coming initially from the psychology field. Based on the fundamental role of this notion in science education, we discuss in this paper its implementation and shows the difficulties met to avoid the different kind of reification. Then, from a specific didactic and epistemological framework (i.e., the problematization), we show how such a framework is involved in the renewal of issues related to conceptions.